Application of Fluorescence-Guided Surgery to Subsurface Cancers Requiring Wide Local Excision: Literature Review and Novel Developments Toward Indirect Visualization. (13th January 2018) - Samkoe, Kimberley S.; Bates, Brent D.; Elliott, Jonathan T.; LaRochelle, Ethan; Gunn, Jason R.; Marra, Kayla; Feldwisch, Joachim; Ramkumar, Dipak B.; Bauer, David F.; Paulsen, Keith D.; Pogue, Brian W.; Henderson, Eric R.
The excision of tumors by wide local excision is challenging because the mass must be removed entirely without ever viewing it directly. Positive margin rates in sarcoma resection remain in the range of 20% to 35% and are associated with increased recurrence and decreased survival. Fluorescence-guided surgery (FGS) may improve surgical accuracy and has been utilized in other surgical specialties. ABY-029, an anti-epidermal growth factor receptor Affibody molecule covalently bound to the near-infrared fluorophore IRDye 800CW, is an excellent candidate for future FGS applications in sarcoma resection; however, conventional methods with direct surface tumor visualization are not immediately applicable. A novel technique involving imaging through a margin of normal tissue is needed. We review the past and present applications of FGS and present a novel concept of indirect FGS for visualizing tumor through a margin of normal tissue and aiding in excising the entire lesion as a single, complete mass with tumor-free margins.